The world philosophy made - Soames, Scott (Princeton University Press, 2019)
How philosophy transformed human knowledge and the world we live inPhilosophical investigation is the root of all human knowledge. Developing new concepts, reinterpreting old truths, and reconceptualizing fundamental questions, philosophy has progressed-and driven human progress-for more than two millennia. In short, we live in a world philosophy made. In this concise history of philosophy's world-shaping impact, Scott Soames demonstrates that the modern world-including its science, technology, and politics-simply would not be possible without the accomplishments of philosophy.Firmly rebutting the misconception of philosophy as ivory-tower thinking, Soames traces its essential contributions to fields as diverse as law and logic, psychology and economics, relativity and rational decision theory. Beginning with the giants of ancient Greek philosophy, The World Philosophy Made chronicles the achievements of the great thinkers, from the medieval and early modern eras to the present. It explores how philosophy has shaped our language, science, mathematics, religion, culture, morality, education, and politics, as well as our understanding of ourselves.Philosophy's idea of rational inquiry as the key to theoretical knowledge and practical wisdom has transformed the world in which we live. From the laws that govern society to the digital technology that permeates modern life, philosophy has opened up new possibilities and set us on more productive paths. The World Philosophy Made explains and illuminates as never before the inexhaustible richness of philosophy and its influence on our individual and collective lives.
9780691176925
Keywords: Philosophy and civilization; Philosophy